Predicting response to repetitive transcranial magnetic stimulation in patients with schizophrenia using structural magnetic resonance imaging: a multisite machine learning analysis - Koutsouleris, Nikolaos; Rietschel, Marcella (Schizophrenia bulletin, 2018)
AbstractBackground. The variability of responses to plasticity-inducing repetitive transcranial magnetic stimulation (rTMS) challenges its successful applicati